Da construção da identidade profissional médica: reflexões teórico-práticas - Mendes, Leandro Manoel Afonso (Universidade Federal de São Carlos, 2024)
The present study, grounded in a critical and reflective analysis of the author's formative journey, sheds light on relevant concepts for the construction of the medical professional identity in students — a theme gaining prominence in various medical schools worldwide, emphasizing the importance of education focused on character development and the promotion of virtues. The objective is to investigate how the constructivist educational model and the integrated theory-practice curriculum, both foundational aspects of the UFSCar medical course, influence identity formation. Additionally, the study seeks to reflect on intrinsic and extrinsic factors affecting students that facilitated or hindered such formation. A qualitative methodological approach was adopted, supported by data triangulation analysis, grounded in extensive systematic reviews and qualitative metasyntheses on the subject. Data were collected and analyzed with a phenomenological emphasis, centered on reading and interpreting entries in the student's reflective portfolio. These were presented in synoptic tables condensing practical elements derived from dialogues with authors, outlining their influence on medical identity construction, and specifying intrinsic/extrinsic facilitators and barriers to formation. The finding that early exposure to professional practice in this educational model significantly and positively influences various aspects of medical professional identity formation is a noteworthy contribution of this study. Similarly, the constant emphasis on activity reflection and encouragement of active learning reinforces the conclusion that new medical courses with constructivist methodologies are more aligned with the identity formation of physicians who genuinely adhere to societal principles. However, areas requiring improvement and constant vigilance were highlighted. More than a synthesis of the student's practical journey, this study constitutes an object contributing to the construction of the author's professional identity. It is the composition of a symphony whose notes are intrinsic to experiences that have been reverently embraced. Revisiting the past illuminates the path of the present, providing insights that transcend time and guide the future journey.
Construction of medical professional identity: theoretical-practical reflections
Keywords: Educação médica; Educação; Educação de graduação em medicina; Estudantes de medicina; Papel do médico; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM